Effect of Enzyme Addition in the Making of Pedro Ximenez Sweet Wines Using Dynamic Pre-fermentative Maceration - Espejo, F.; Armada, S. (South African Journal of Enology and Viticulture, 2016)
This work evaluated the effect of two commercial pectolytic enzymes on some oenological parameters before and after enzymatic treatments with pre-fermentative dynamic maceration at room temperature for three hours. The study was conducted on an industrial scale using musts from sun-dried grapes of the Pedro Ximenez variety. Statistical analysis and sensory rating showed that the resulting wines varied significantly in total soluble solids (ºBrix) and in the final sensorial controls. On the other hand, the enzyme treatment had no effect on the content of total polyphenols (TPI) and other chemical characteristics of the obtained musts. A higher qualitative level was observed with regard to aroma and gustative quality compared to the control. The results also demonstrate that total juice yield improved after enzyme addition together with dynamic maceration.